2012
DOI: 10.1016/j.destud.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Methodological insights from a rigorous small scale design experiment

Abstract: This paper discusses the methods used to conduct high quality small-scale design experiments. It aims to provide a demonstrator promoting the uptake of more rigorous methods in design research and based on this it aims to specify a body of further work for linking study types and contexts. A small-scale experiment was conducted using methods specifically developed to mitigate four core problem areas identified from review: context, system understanding, methods and controls. The techniques were then critiqued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 57 publications
2
26
0
Order By: Relevance
“…This is in line with some prior gesture studies (Yasui, 2013) and previous surveys of team size effects (Cash, Elias, Dekoninck, & Culley, 2012). In particular dyads have been shown to display different generic communication behaviour to larger groups (Hackman & Vidmar, 1970;Salas et al, 2008) while teams of three have been found to be analogous to teams of up to five people (Cash et al, 2012;Hackman & Vidmar, 1970).…”
Section: Populationsupporting
confidence: 76%
“…This is in line with some prior gesture studies (Yasui, 2013) and previous surveys of team size effects (Cash, Elias, Dekoninck, & Culley, 2012). In particular dyads have been shown to display different generic communication behaviour to larger groups (Hackman & Vidmar, 1970;Salas et al, 2008) while teams of three have been found to be analogous to teams of up to five people (Cash et al, 2012;Hackman & Vidmar, 1970).…”
Section: Populationsupporting
confidence: 76%
“…Twelve students were randomly selected and split into four teams of three. A team size of three was selected as it fulfilled the demands of representativeness (Cash, Elias, et al, 2011), whilst also allowing for effective comparison to the activities of the practitioners in Study 1.…”
Section: Specific Differencesmentioning
confidence: 99%
“…While this measure was not expected to have a positive influence, it was used to give the participants the impression of receiving helpful support emulating the effects of what in medical trials is referred to as a placebo (Cash et al, 2012).…”
Section: Design Experiments Moon Landingmentioning
confidence: 99%